(untitled) (European Journal of Pure and Applied Mathematics, 2024)
The primary aim of this paper is to explore the behavior of several nonlinear systems of difference equations following T_n+1=(E_nE_n-4)/(T_n-3(± 1 ± E_nE_n-4)), E_n+1=(T_nT_n-4)/(E_n-3(pm 1 ± T_nT_n-4)), and obtain solution expressions for them. Moreover, we utilize MATLAB programming to simulare the dynamics and validate our results.